Desires and taboos: Sexual relationships between coaches and athletes - Johansson, S.; Kenttä, G.; Andersen, M. B. (International Journal of Sports Science & Coaching, 2016)
Coach-athlete sexual relationships constitute ethical, behavioral, social, and emotional quandaries that are rarely addressed openly. Most of the current body of research in this area focuses on coaches` sexual harassment and abuse of children and female athletes. In the present article, we discuss legal coach-athlete sexual relationships and adopt a coach perspective. As dual relationships, coach-athlete sexual relationships blur the boundaries between professional roles circumscribed (usually) by ethical codes of conduct and private spheres of love and desire. We explore the problems associated with the limitations of dichotomous right/wrong ethical decision making and discuss additional ways to understand these relationships, accounting for coaches` and athletes` well-being, performance, gendered sexual agency, power, ethical dilemmas, sport policy, and legal implications. Our discussion raises questions about how to open up dialogue and transparency regarding coach-athlete sexual relationships and how to facilitate functional, healthy coach-athlete relationships. Finally, we provide implications for future research that include legal and consensual coach-athlete sexual relationships and advocate transparency, open discussion, and coach education about coach-athlete sexual relationship dilemmas. ABSTRACT FROM AUTHOR